Sovereign Wealth Funds : Aspects of Governance Structures and Investment Management - Al-Hassan, Abdullah; Papaioannou, Michael; Skancke, Martin; Sung, Cheng Chih. (Washington, D.C. : International Monetary Fund, 2013)
This paper presents in a systematic (normative) manner the salient features of a SWF's governance structure, in relation to its objectives and investment management that can ensure its efficient operation and enhance its financial performance. In this context, it distinguishes among the various governing bodies and analyzes key aspects of the investment policy and setting of the risk tolerance level in order to ensure consistent risk-bearing capacity and greater accountability. Further, it discusses the important role of SWFs in macroeconomic management and the need for close coordination with other macroeconomic and financial policies as well as their role in global financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet